Long working hours and self-rated health: Evidence from Beijing, China. (December 2019) - Wu, Wenjie; Chen, Yiyi; Stephens, Mark; Liu, Ye
Abstract: Western research has shown that working long hours have detrimental effect on health. This paper examines the relationship between long working hours and self-rated health in Chinese cities, using data from a large-scale questionnaire survey in Beijing. The results show that individuals who report long working hours are more likely to report poor health. Migrant workers who report long working hours are more likely to report poor health than urban workers. We also find that the relationship between long working hours and self-rated health varies by occupation. Additional results provide an insight into the contextualized dependent nature of the interaction effect of commuting time and long working hours on self-rated health. Highlights: Individuals who report long working hours are more likely to report poor health. The relationship between long working hours and self-rated health varies by occupation. There is an interaction effect of commuting time and long working hours on self-rated health.